ChemInform Abstract: Recent Development of Phosphorylases Possessing Large Potential for Oligosaccharide Synthesis. Issue 25 (3rd June 2013) - Nakai, Hiroyuki; Kitaoka, Motomitsu; Svensson, Birte; Ohtsubo, Ken'ichi
Abstract Review: 66 refs.